PERIBAHASA DALAM BAHASA MELAYU DIALEK SAMBAS - Nia Lestari; Ahadi Sulissusiawan; Agus Wartiningsih (Universitas Tanjungpura, 2019)
AbstractThis research is aimed to describe the using of the types, meanings and functions of proverbs in the Malay language of the Sambas dialect.The method used in this research is descriptive method with qualitative research. The data source in this study was Malay language of the Sambas dialect native speaker who obtained through direct observation and field recording. The data in this study are related to the types, meanings, and functions of proverbs. The technique used in this study is the conversational listening technique that has a basic technique in the form of provoking to speakers who are native speakers of the Malay language of the Sambas dialect. Data collection tools used in this study were interview instruments, video recorders, and voice recorders. Based on the results of research and data analysis, it can be concluded that the types of proverbs can be found, they are the aphorism of 26 proverbs, parables of 19 proverbs, idiom of 15 proverbs, slogan of 3 proverbs, parable of 4 proverbs, and simile of 2 proverbs The meaning of proverbs is analyzed in terms of denotation (true meaning) and connotation (figurative meaning). The function of the proverb is the advice of 15 proverbs, satire of 32 proverbs, praise of 3 proverbs, and diplomacy or affirmation of 3 proverbs.Keywords: functions, meanings, and types of proverbs